PENERAPAN ANALISIS FAKTOR UNTUK MENGIDENTIFIKASI FAKTOR – FAKTOR YANG MEMPENGARUHI KEPUASAN KONSUMEN TERHADAP PENJUALAN SARI ROTI - Sri Sukmawati; Jamilludin Fikri; Oman Sahroni (LPPM Universitas Bina Bangsa, 2023)
This study aims to apply factor analysis to identify factors that affect consumer satisfaction with bread cider sales. Consumer satisfaction is a key factor that affects the success of a business, especially in the food and beverage industry. In the context of cider sales, factors that can affect consumer satisfaction include product quality, price, customer service, and brand image. The research method used is a survey using a structured questionnaire. The sample of this study is consumers who have purchased and consumed bread juice within a certain period of time. The collected data is analyzed using factor analysis techniques to identify factors that are significant in influencing consumer satisfaction. The results showed that there are several factors that play an important role in influencing consumer satisfaction with bread cider sales. These factors include product quality, affordable prices, friendly and responsive customer service, and a positive brand image. Product quality is the most dominant factor affecting customer satisfaction, followed by customer service and price. In addition, brand image also has a significant influence on consumer satisfaction. The results of this study have important implications for sari roti business managers in increasing consumer satisfaction and their sales. By understanding the factors that affect customer satisfaction, business managers can take strategic steps in improving product quality, improving customer service, and strengthening their brand image. This research can also be a reference for future research on consumer satisfaction in the food and beverage industry, especially in bakery products